Home range, habitat use, and activity patterns of African wolves (Canis lupaster) in the Ethiopian highlands - Tariku Mekonnen Gutema; Anagaw Atickem; Diress Tsegaye; Desalegn Chala; Afework Bekele; Claudio Sillero-Zubiri; Jorgelina Marino; Dietmar Zinner; Vivek V. Venkataraman; Peter J. Fashing; Nils C. Stenseth (Global Ecology and Conservation, 2022)
African wolves (Canis lupaster) and Ethiopian wolves (C. simensis) occur often sympatrically across habitats in the Ethiopian Highlands, with recent studies finding evidence for interspecific competition. However, unlike the well-studied Ethiopian wolf, comparatively little is known about the ecology of the African wolf in the Ethiopian Highlands. To address this empirical gap, we collected data on home range size, habitat use, and activity patterns of radio-collared African wolves at the Guassa Menz Community Conservation Area (GCCA) and Borena Saynt Worehimenu National Park (BSNP). We followed the African wolves (5 in GCCA, 6 in BSNP) for 16 months and had 659 ± 83 encounters with each individual. The mean 95% kernel density estimate home range size of African wolves was higher in BSNP (4.5 ± 1.5 km2) than at GCCA (2.2 ± 0.7 km2). In 55% (n = 3934) of the encounters the wolves were found to be solitary, whereas in other encounters we found them in groups of two to seven. At both sites, the African wolves were more often found in areas close to human settlements than in more intact habitat, and they were mainly active at dawn and dusk. These results show flexibility in African wolf socioecology in response to habitat fragmentation and anthropogenic disturbance. We recommend further studies on major causes of spatial and temporal niche partitioning of Ethiopian wolves and African wolves in the Ethiopian Highlands.